2007
DOI: 10.2139/ssrn.976074
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Cooperation, and Implementation of Sustainability Programs: The Case of Local Agenda 21

Abstract: This paper provides evidence of the role of trust in ensuring desirable economic outcomes. We examine the implementation of Local Agenda 21, a regional sustainability initiative that requires the coordination of diverse decision-makers, in a sample of approximately 66 developing and industrialized countries. We use a game theoretic framework to motivate our empirical study of the number of Local Agenda 21 programs implemented across countries. We find that higher levels of aggregate trust are associated with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…and mentioned in her work. Her intuition is included in the analysis of Grafton and Knowles (2004) and supported by the empirical evidence of Owen and Videras (2008). In a cross-sectional examination of 66 countries, the latter find that trust is positively correlated with the amount of local Agenda 21 programmes implemented in a given place.…”
Section: Linking Trust and Greenhouse Gas Emissionsmentioning
confidence: 83%
See 1 more Smart Citation
“…and mentioned in her work. Her intuition is included in the analysis of Grafton and Knowles (2004) and supported by the empirical evidence of Owen and Videras (2008). In a cross-sectional examination of 66 countries, the latter find that trust is positively correlated with the amount of local Agenda 21 programmes implemented in a given place.…”
Section: Linking Trust and Greenhouse Gas Emissionsmentioning
confidence: 83%
“…If benefits from being green exceed the cost differential, the total payoff (i.e. Her intuition is included in the analysis of Grafton and Knowles (2004) and supported by the empirical evidence of Owen and Videras (2008). Empirical evidence from a choice experiment supports this formalization: testing the willingness-to-pay of Swedish students to withdraw emissions allowances from the European carbon trading market, Lindman et al (2013) show that the expected participation rates at the population level have a positive effect on students' voluntary participation in the carbon market.…”
Section: Linking Trust and Greenhouse Gas Emissionsmentioning
confidence: 95%
“…The question was raised as to what could be considered to be credible evidence, reinforcing a need for a better understanding of respondents' perception of source credibility (e.g. Ostman and Parkes, 1987;McCallum et al, 1991;Owen and Virderas, 2008).…”
Section: Attitudinal and Normative Beliefmentioning
confidence: 99%
“…Agenda 21 is the main international reference for the implementation of sustainable development through the involvement of local groups of interest. There are several studies about implementing instruments available to local government to assess the strengths and weaknesses point and provide good practices [15][16][17][18][19]. The growing interest of both internal and external stakeholders in companies' activities has led many organizations to adopt EMS certification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The network was governed by a non-hierarchical decision-making structure which deals with public interest issues [11] reducing the participation gap. Over the years, several studies have demonstrated how the ability to involve the different categories of local stakeholders is crucial to improve significantly the quality of regional environment [18]. In 2004 it a survey has been carried out which showed that in Italy the adoption of Local Agenda 21 had a considerable spread, targeting more than 800 Local Authorities.…”
Section: International Communitymentioning
confidence: 99%